(untitled) (Orthodontic Journal of Nepal, 2025)
Introduction: Sella turcica, located in the sphenoid bone, is an important structure in lateral cephalometric analysis. There is a close association of the sella turcica with craniofacial bone development. This landmark is related to the development of the maxillomandibular complex and malocclusions and is commonly used for orthodontic diagnosis and management. It is important for an orthodontist to have a knowledge about morphology of sella turcica and its association with different skeletal patterns. The purpose of this study was to identify the association between sella turcica variations and Skeletal Class I, II and III malocclusions. Materials and Methods: A cross-sectional study was conducted from 1st May, 2024 to 31st October, 2024 on a total of 366 lateral cephalogram records of patients with three different skeletal patterns visiting Samaj Dental Hospital for their orthodontic treatment. The lateral cephalograms were traced digitally using the Webceph software and classified into three groups as skeletal class I, II and III. Shape of sella turcica was assessed. The association between these variations and different skeletal patterns were analysed using the Statistical Package for Social Sciences. Results: Among 366 participants, the mean ANB angle was 3.79˚, with standard deviation of 2.95˚. The study showed that the association between skeletal class and sella turcica morphology was statistically significant (p-value = 0.001). The association between sella turcica morphology and sex of the participants was not statistically significant (p-value = 0.093). Conclusion: There is an association between sella turcica morphology and different skeletal patterns.